(untitled) (The Review of Diabetic Studies, 2025)
Background: Patient satisfaction in the high-pressure environment of the emergency department (ED) is heavily influenced by staff responsiveness, communication, and attentiveness. Hourly rounding, a structured practice of proactive patient checks, has been proposed as a strategy to improve the patient experience by anticipating needs and enhancing engagement. Methods: A quantitative, quasi-experimental study was conducted to evaluate the effect of a structured hourly rounding protocol on patient satisfaction. A sample of 150 adult ED patients was selected using purposive sampling. Data on patient satisfaction were collected in two phases—pre- and post-intervention—using a validated questionnaire that measured overall satisfaction and specific dimensions like communication, responsiveness, and comfort. Data were analyzed using descriptive and inferential statistics. Results: The implementation of hourly rounding led to significant improvements in all measured areas of patient satisfaction. The proportion of patients reporting being "Very Satisfied" overall increased from 20% to 50%. Satisfaction with staff communication rated as "Excellent" rose from 16.7% to 46.7%. Perceptions of staff responsiveness rated as "Excellent" increased from 13.3% to 43.3%. Furthermore, excellent ratings for comfort and safety increased fourfold, from 10% to 40%. Conclusion: The findings demonstrate that the systematic implementation of hourly rounding by ED staff significantly enhances patient satisfaction across multiple domains, including communication, responsiveness, comfort, and safety. This proactive, structured approach is an effective intervention for improving the patient experience and overall quality of care in emergency settings.